Measurement and analysis of the impact of transverse incoherent wakefields in a light source storage ring - P. Brunelle; R. Nagaoka; R. Sreedharan (Physical Review Accelerators and Beams, 2016)
The influence of incoherent wakefields arising from a high current beam circulating in a ring composed of many flat chambers on the beam is analyzed numerically and experimentally for the SOLEIL storage ring. Three distinct ranges of the excited field are studied: the long multiturn regime in multibunch fillings, the medium regime involving neighboring bunches, and the short intrabunch regime. Two theoretical models, which both take into account the field diffusion across chamber walls of finite thickness, are employed to compare the measurement with theoretical expectations. Specific experimental methods, based respectively upon orbit analysis, bunch-by-bunch transverse feedback and a single particle betatron resonance, are introduced to measure the incoherent focusing effect in the three regimes. It is found that the excited incoherent fields can be large enough to affect the ring performance. The non-negligible contribution of nonevaporable getter coating is shown to improve the agreement between measurements and calculations.